2023
DOI: 10.3390/v15020298
|View full text |Cite
|
Sign up to set email alerts
|

Dual Infection of Hepatitis A Virus and Hepatitis E Virus— What Is Known?

Abstract: Viral hepatitis is an infection of human hepatocytes resulting in liver damage. Dual infection of two hepatotropic viruses affects disease outcomes. The hepatitis A virus (HAV) and hepatitis E virus (HEV) are two enterically transmitted viruses; they are positive single-stranded RNA viruses and have common modes of transmission. They are transmitted mainly by the fecal-oral route and ingestion of contaminated food, though the HAV has no animal reservoirs. The HAV and HEV cause acute self-limiting disease; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 132 publications
0
30
0
Order By: Relevance
“…An HAV/HEV double infection can also lead to complications like acalculous cystitis and hepatic neuropathy, which are the worst possible outcomes. As evidenced by liver abnormalities and liver function tests, other studies support the conclusion that HEV/HAV double infection can cause a severe disease course [ 6 , 9 - 10 ]. Similarly, Paul et al reported a higher mortality rate for HEV infections in pregnant women.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…An HAV/HEV double infection can also lead to complications like acalculous cystitis and hepatic neuropathy, which are the worst possible outcomes. As evidenced by liver abnormalities and liver function tests, other studies support the conclusion that HEV/HAV double infection can cause a severe disease course [ 6 , 9 - 10 ]. Similarly, Paul et al reported a higher mortality rate for HEV infections in pregnant women.…”
Section: Discussionmentioning
confidence: 75%
“…The pattern and rate of transmission are primarily influenced by socioeconomic variables. Lower infection rates are observed in areas with smaller families, better sanitation facilities, and greater access to clean water [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study has indeed shown a higher presence of anti-HAV and anti-HEV in men who have sex with men [ 109 ]. These conflicting data may be due to geographical biases, risk factors and viral genotypes, so further studies are needed to evaluate the prevalence and outcomes of dual infection [ 110 ].…”
Section: Hev Infection Overviewmentioning
confidence: 99%